Biodiesel synthesis from Hevea brasiliensis oil employing carbon supported heterogeneous catalyst: Optimization by Taguchi method. (April 2016) - Dhawane, Sumit H.; Kumar, Tarkeshwar; Halder, Gopinath
Abstract: The present work illustrates the parametric effects on biodiesel production from Hevea brasiliensis oil (HBO) using flamboyant pods derived carbonaceous heterogeneous catalyst. Activated carbon (AC) was prepared maintaining 500 °C for 1 h and steam activated at optimised values of activation time 1.5 h and temperature 350 °C. Carbonaceous support was impregnated with KOH at different AC/KOH ratios. The transesterification process was optimized and significant parameters affecting the biodiesel yield was identified by Taguchi method considering four parameters viz. reaction time, reaction temperature, methanol to oil ratio and catalyst loading. The physicochemical properties of Hevea brasiliensis methyl ester (HBME) were examined experimentally at optimised condition and found to meet the global American standards for testing and materials (ASTM). The optimum condition observed to yield 89.81% of biodiesel were: reaction time 60 min, reaction temperature 55 °C, catalyst loading 3.5wt% and methanol to oil ratio 15:1. Contribution factor revealed that among four parameters considered, catalyst loading and methanol to oil ratio have more prominent effect on biodiesel yield. The cost for preparing carbonaceous catalyst support was estimated and observed to be fairly impressive. Thus, Hevea brasiliensis oil (HBO) could be considered as suitable feedstock and flamboyant pods derived carbon as effective catalyst for production of biodiesel. Highlights: Study of parametric effects on transesterification of HBO by carbonaceous catalyst. Taguchi method with L9 orthogonal array was used for optimization of the process. Catalyst loading was emerged as most influential parameter. Cost analysis of catalyst revealed that it is cost effective and eco-friendly. Biodiesel was characterised following ASTM standards.